(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Underground coal mines are always faced with their own specific uncertainties. These uncertainties lead to safety risks and ultimately result in chaos and safety disturbances. Human factors are among the uncertainties that play a vital role in various industries, including underground coal mining. For instance, they affect safety, production processes, machinery maintenance, and productivity. Risk management is one of the primary methods for improving safety in underground coal mines. Risk management is a process that helps identify, assess, and mitigate risks and uncertainties. Its main goal is to protect resources, enhance safety, and increase efficiency through informed decision-making. This article examines the role of human factors in risk assessment of coal mines; it first classifies human factors and then uses the Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (Fuzzy-TOPSIS) method for pairwise comparison to evaluate the risks of underground coal mines. The TOPSIS method is a multi-criteria decision-making technique that operates based on the distance of options from the best and worst solutions. This method ranks the options based on specific criteria and assists in selecting the optimal option. The results of the study on human factors indicated that carelessness, negligence, and distraction had the greatest impact on the risk assessment of underground coal mines, with a similarity index of 0.6516, while the level of education had the least impact with a similarity index of 0.2871.